Some Transformation Properties with Omitted Value - Mazloum, Fatima AH.; Alhily, Shatha S. (Iraqi Journal of Science, 2023)
The purpose of this  paper is to show that for a holomorphic and univalent function in class S, an omitted –value transformation  yields a class of starlike functions as a rotation transformation of  the Koebe function, allowing both the image and rotation of the function   to be connected. Furthermore, these functions have several properties that are not far from a convexity properties. We also show that Pre- Schwarzian derivative is not invariant since the convexity property of the function   is so weak.